Tuning Photoinduced Electron Transfer in POM‐Bodipy Hybrids by Controlling the Environment: Experiment and Theory - Toupalas, Georgios; Karlsson, Joshua; Black, Fiona A.; Masip‐Sánchez, Albert; López, Xavier; Ben M'Barek, Youssef; Blanchard, Sébastien; Proust, Anna; Alves, Sandra; Chabera, Pavel; Clark, Ian P.; Pullerits, Tönu; et al. (Angewandte Chemie International Edition, 2021)
The optical and electrochemical properties of a series of polyoxometalate (POM) oxoclusters decorated with two bodipy (boron‐dipyrromethene) light‐harvesting units were examined. Evaluated here in this polyanionic donor‐acceptor system is the effect of the solvent and associated counterions on the intramolecular photoinduced electron transfer. The results show that both solvents and counterions have a major impact upon the energy of the charge‐transfer state by modifying the solvation shell around the POMs. This modification leads to a significantly shorter charge separation time in the case of smaller counterion and slower charge recombination in a less polar solvent. These results were rationalized in terms of Marcus theory and show that solvent and counterion both affect the driving force for photoinduced electron transfer and the reorganization energy. This was corroborated with theoretical investigations combining DFT and molecular dynamics simulations. The intramolecular photoinduced electron transfer of a series of polyoxometalate (POM)‐bodipy hybrids was examined. The data show that both solvents and counterions have a major impact on the relaxation dynamics of the excited states by modifying the solvation shell around the POM. The experimental findings were corroborated with a computational investigation combining DFT and molecular dynamics simulation methods.